"Cheerful or Merry?" Investigating Literary Translation Revision. Issue 1 (April 2020) - JACCOMARD, HÉLÈNE
Abstract : In this paper I discuss the process of revision undergone by my translation into English of Yasmina Reza's play Dans la luge d'Arthur Schopenhauer. Once the first draft was completed and in order to produce a natural-sounding final draft, I carried out a self-revision in collaboration with an English native-speaker, a playwright with some experience in transcreation . I will show how our respective interlanguages affected the final choices made. A corpus-based study comparing the first draft with the final draft demonstrates that a largely unconscious adherence to translation norms and the reviser's stylistic preferences both converge to arrive at a translation for the stage rather than the page. This paper confirms the importance of translation revision and how the process can be improved with the use of simple digital tools.